Large Temporoparietal Cranioplasty by Customized Prosthesis: A Case Report - Omid Ghaderzadeh; Sarvin Soleymanipoor; Seyed Roholah Ghodsi; Zahra Namazi (Case Reports in Clinical Practice)
A 15-year-old male presented at a neurosurgeon’s office following a traffic accident. A CT scan revealed bone deficiency in the temporoparietal area. The surgical solution involved implanting a 3D-printed prosthesis into the skull. Axial 3D created the model using stereolithography 3D printing technology with Poly Methyl Methacrylate (PMMA). The use of 3D printing as a surgical aid is gaining popularity. Our experience with the presurgical model demonstrates its utility in individualized surgical planning for skull defects.